Breaking bad news. Issue 6 (November 2016) - Kirby, Roger
Abstract : Looking back over my career, I think one of the very hardest things that I have ever had to do was tell the parents of a teenage motorcyclist, brought in seriously injured to Accident and Emergency, that we were unable to save him from the catastrophic bleeding resulting from his shattered liver and spleen. Breaking bad news goes with the territory of being a doctor, yet we seldom stop and think how best it can and should be done.